2019
DOI: 10.5114/hm.2019.83997
|View full text |Cite
|
Sign up to set email alerts
|

Selected personal conditions determining the frequency of consuming groups of products among athletes professionally training individual sports disciplines

Abstract: Purpose. Evaluation of the frequency of consuming food products depending on sex, age, and level of self-efficacy, optimism and life satisfaction in a group of athletes professionally training individual sports disciplines. Methods. the research was performed among 346 individuals (214 men and 132 women). the author's personal consumption questionnaire, the General Self-Efficacy Scale, the Life Orientation test-revised, and the Satisfaction with Life Scale were used. the Mann-Whitney U test, the Kruskal-Wallis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 26 publications
(53 reference statements)
0
12
0
Order By: Relevance
“…Therefore, the indicated trends were ambiguous, nonetheless, they may suggest greater nutritional awareness and/or attaching greater attention to food choices with age, in relation to the state of health and an increase in belief in the significant role of diet for exercise capacity, determining the effective performance of refereeing functions. Trends indicating more rational nutritional behaviours along with age (as well as experience and sports level) have also been described among athletes training team sports (Kopeć et al, 2013;Gacek, 2018a) and individual disciplines (Gacek, 2019). Among athletes training individual disciplines, it has been shown that with age, the players significantly more often included poultry and mineral water in their diet, and significantly less often milk with high fat content, pork, sweets and confectionery products (Gacek, 2019).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Therefore, the indicated trends were ambiguous, nonetheless, they may suggest greater nutritional awareness and/or attaching greater attention to food choices with age, in relation to the state of health and an increase in belief in the significant role of diet for exercise capacity, determining the effective performance of refereeing functions. Trends indicating more rational nutritional behaviours along with age (as well as experience and sports level) have also been described among athletes training team sports (Kopeć et al, 2013;Gacek, 2018a) and individual disciplines (Gacek, 2019). Among athletes training individual disciplines, it has been shown that with age, the players significantly more often included poultry and mineral water in their diet, and significantly less often milk with high fat content, pork, sweets and confectionery products (Gacek, 2019).…”
Section: Discussionmentioning
confidence: 90%
“…The sense of self-efficacy, derived from Bandura's theory of social learning, is the belief in having the ability to achieve intended goals, such as those related to health, which can be fostered by rational nutritional behaviours (Juczyński, 2012). In existing studies on athletes, it has been shown that eating behaviours can be related to age, professional experience and sport level (Gacek, 2018a(Gacek, , 2019 and the level of generalised selfefficacy (Gacek, 2015(Gacek, , 2019, with an indication of a tendency towards more rational behaviours among athletes with greater experience and representing higher sporting levels (Kopeć, Nowacka, Klaja, Leszczyńska, 2013;Gacek, 2018aGacek, , 2019, and those with a higher sense of self-efficacy (Gacek, 2015(Gacek, , 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Trends for more No 1 rational women's food choices than men have also been described among high-class Portuguese athletes during the preparatory and starting periods [34]. Also, in other Polish studies among athletes training individual disciplines and team sports, tendencies towards more rational dietary behaviours of women than men have been shown, which are particularly related to the more frequent consumption of raw vegetables and dairy products with reduced fat content [13,18]. The consumption of less recommended products (rich in saturated fatty acids and/or simple sugars) more widespread among the surveyed men corresponded to the tendencies shown among Polish athletes training team games [13], and the youth of Warsaw sports schools [28] as well as American sports students [25].…”
Section: Discussionmentioning
confidence: 91%
“…Mistakes and qualitative nutritional errors found in the examined group of athletes, generally corresponded to the trends described in other studies conducted at both Polish and foreign centres, among competitive athletes of various disciplines. In these studies, the inadequate consumption of some groups of foods with high nutritional density was confirmed, including vegetables and fruits, wholegrains, dairy products and fish, considering Polish athletes participating in team [13] and individual disciplines [18], as well as Spanish [44], Iranian [27] and Portuguese athletes [34], as well as English and Australian footballers [26,35], Irish and British rugby players [1,45], Lithuanian athletes of endurance disciplines [3], women training mediumand long-distance running [22] and rally drivers [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation